It's an iPhone world--we just live in it. (Mac life)
Together, the iPhone 3.0 OS update and iPhone 3Gs offer faster Web surfing, gaming, and twittering than ever. Here's what's new in the iPhone OS and accessible to all iPhone users. We also review the 3Gs, the fastest, slickest, most fun iPhone yet.